Prone positioning acute respiratory distress syndrome patients - Guérin, Claude (Journal of Thoracic Disease; Vol 10, Supplement 17 (June 20, 2018): Journal of Thoracic Disease, 2018)
I read with great interest the editorials of my esteemed colleagues regarding the Apronet study (1). This study aimed at making a picture of the use of prone position (PP) in acute respiratory distress syndrome (ARDS) in the current time and to explore the reasons to not proning these patients. I thank Journal of Thoracic Disease (JTD) for providing me the opportunity to share some comments with them.